PENGGUNAAN MEDIA PEMBELAJARAN CROSSWORD PUZZLE (TEKA-TEKI SILANG) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA - Ratri Nuryani Qudwathullatifah; Gina Tuty Alawiyah (Institut Pendidikan dan Bahasa Invada, 2020)
This research is motivated by the low ability of students to multiply two fractions which is influenced by several factors including conventional learning and some students cannot do multiplication. This makes the ability of students to multiply two fractions is still low. Based on these problems, efforts to improve students' ability to multiply two fractions by using a cooperative model type TAI (Team Assisted Individualization). This research method uses Classroom Action Research which consists of four stages, namely; planning, implementation, observation, and reflection. This research was carried out in two cycles, where from each cycle there was a significant increase so that the TAI learning model could be applied to Mathematics.increase, namely the acquisition of the percentage value of teacher skills in the first cycle of 77%, in the second cycle of 93 %. The value of the percentage of student activity in the first cycle was 79%, in the second cycle it was 95%. The percentage value of students' creative thinking skills in the first cycle was 69%, in the second cycle it was 84%. Thus it can be seen that the use of crossword puzzle learning media that researchers apply in the learning process can improve students' creative thinking skills